The Impact of E-Commerce on Digital Marketing Hopes And Ambitions: A Case Study in Airline Reservation Offices in Iraq - Maaroof *, Anas; Oğrak, Abdullah (Journal of Economics and Administrative Sciences, 2024)
Purpose: The current study aims to identify the impact of e-commerce with digital marketing in airline reservation offices in the Republic of Iraq. The study consists of two main variables: the independent variable that included e-commerce, which consisted of four dimensions: Business-to-Business, Consumer-to-Business, and Consumer-to. - Consumer, Business-to-Government, and the dependent variable represents digital marketing, the dimensions of which are: website design, social media marketing, search engine optimization, and email marketing.Theoretical Framework: Upon on Maaroof, A. (2021) This study highlights the importance of e-commerce and digital marketing, such as booking corners during digital transactions in airline reservation offices, as well as the most important challenges facing customers and reservation offices.Design/ Methodology/ Approach: As for the practical aspect, the airline reservation offices were taken and included the governorates (Nineveh, Erbil, Dohuk, Kirkuk, Tikrit and Baghdad), and 250 questionnaires were accepted as valid questionnaires and were analyzed accordingly. To determine the relationship between the study variables, two main hypotheses and sub-hypotheses were proposed and tested using several statistical methods in Analysis of Moment Structures AMOS (V.24).Findings The results emphasize that there is a positive correlation and impact between all dimensions of e-commerce (Business-to-Business, Consumer-to-Business, Consumer-to-Consumer and Business-to-Government). The results also showed that activating the role of e-commerce has a positive impact on digital marketing at airline reservation offices in the Republic of Iraq.Research Implications: In addition, the study presented several recommendations for airline booking companies. For example, there is an increased interest in airline reservation companies to adopt the philosophy of e-commerce, as it has an impact on increasing market share, which ensures their continuity and success.Originality/Value: Originality/value: This study works to enhance the adaptation of e-commerce applications for airline reservation companies in the Republic of Iraq through customers’ use of applications, and in addition to bridging the digital divide, which is the feeling of many customers’ anxiety about using applications.